Panorama laser lane system based IoT - Won Bang, Gul; Ho Kim, Yong (International Journal of Engineering and Technology, 2018)
Background/Objectives: Lane marking to recognize road condition helps driver safely drive. Device in this study is developed as a complement because existing lane marking is able to difficult to identify lane according to its environment.Methods/Statistical analysis: Lane marking has been built by spraying tiny particles of glass on a paint for the purpose of retro-reflection against headlamps in automobile at night. But paint with tiny particles of glass is eliminated by automobiles and function of retro-reflection tends to lost over time. That makes lanes invisible well on rainy days at night. Panorama laser lane system based on mobile network with remote control is designed to irradiate laser beam sequentially toward the road on rainy or snowy day at night for safety guidance.Findings: The system provides visible lane markings on rainy days or at night because laser beam lights the lane on the road to help avoid traffic accident.Improvements/Applications: Smart road to provide safety drive will be built by the installation of system at 20 meters in the road particularly dangerous section of road or accident black spot.Â